(untitled) (Justicia &Derecho, 2021)
The following case law analysis addresses the Supreme Court ruling issued on April 13th, 2020, which invalidated a Santiago Court of Appeal decision, stating that the procedural burden consisting of allocating sufficient funds aimed to continue the proceedings associated to a cassation, does not apply to those cases filed before Law N° 20.886 entered into force, according to its transitory provisions and, as consequence, the abandonment of such recourse is against the law. The analysis also scrutinizes the main motivations raised by the Supreme Court ruling in the light of other judgments issued by the Supreme Court and examines its ratio decidendi under the legislative history, jurist opinions and the various bodies of law that governs the Chilean neophyte digital legal system.